Effect of Different Levels of Egg Shell in Diet on the Production Performance, Egg Quality and Heavy Metal Contents in Laying Hens - Hassan , M.R.; Naushinara, A.S.; Sultana, S.; Rabbani, M.A.G.; Faruque, S.; Shammi, M.; Rahman, M.M.; Khabiruddin, M.; Sultana, N. (International Journal of Poultry Science, 2022)
Background and Objective: In Bangladesh, huge amount of eggshell-waste is produced every day. Most of them are discarded into the environment. However, it can be a resource upon proper management. As eggshell contains around 40% calcium which is beneficial as poultry feed. Therefore, the present experiment was conducted to convert eggshell-waste as a dietary source of laying hen. Materials and Methods: In this experiment, a total of 50 kg of eggshell was collected from farm and local food vendors. At 30 weeks of age, a total of 100 laying hens were randomly selected and were divided into 5 groups with 4 replications. The treatments were: T0: Control group-100% limestone, T1: 75% limestone and 25% eggshell based-feed, T2: 50% limestone and 50% eggshell based-feed, T3: 25% limestone and 75% eggshell based-feed and T4: 100% eggshell-feed. The hens were fed with 120 g/hen/day and water was provided ad-libitum during the experiment. The standard management system was followed. Results: A significantly higher egg weight and eggshell weight was found by feeding of 100% eggshell based-feed treatment (p<0.05). No significant differences were observed in the laying performance, egg production, body weight and egg quality among the treatments but the eggshell breaking strength was improved by using eggshell as poultry feed. Therefore, 3.80 kg/cm2 egg-shell breaking strength was found in 100% eggshell-feed which was numerically higher among the treatments. Inclusion of eggshell to the laying hen diet resulted in similar production performance and egg qualities compared to those of control. On the other hand, heavy metals (Pb, Cr, Cd) concentration followed in decreasing trend. Therefore, Egg shell would be a good source of poultry feed. Conclusion: Based on the experiment it can be concluded that eggshell may be used as an alternative source of calcium rather than throwing as waste.